Cooperative Learning Methods for Improving Achievement in the Subject of Electrical Engineering and Energy Conversion in Class X Students of Mechanical Engineering at SMK Negeri 2 Samarinda - Boyong, Fredrik (PT Literasi Nusantara Publisher, 2022)
This study aims to determine the improvement of student learning achievement taught by cooperative learning methods in the subject of machine electricity and energy conversion. This type of research is classroom action research. The subject of this study where 32 students of mechanical engineering class X TP. Data was collected using a written test. Data were analyzed using descriptive quantitative. The results of this study are the methods applied by making the class a total of 16 students. Students are required to learn to speak, the teacher appoints a student to explain a material, the material is determined and taken from a learning media slide. Students explain to classmates, if the student's explanation cannot be understood by all students, the teacher explains it until the material can be understood. All students will have the opportunity to advance to explain the material. Cycle I there is an increase in student learning achievement by 8.89%. Cycle II, there was an increase in student learning achievement by 2.92%. Cycle III there is an increase in student learning achievement by 4.46%.